Exploring the beneficial endophytes of Zingiberaceae - Mohd Rosli, Norsalsabila; Ponari, Md Hoirul Azri; Meenakshi Sundram, Tamil Chelvan; Zainuddin, Zarina; Yunus, Muhamad Fahmi (Faculty of Biotechnology and Food Sciences, Slovak University of Agriculture, 2024)
Sustainable agriculture in combination with crop improvement programme is gaining more attention in the scientific field nowadays. With abundance of resources, endophytes offer an environmentally friendly and sustainable approach to increase crop yield, improve soil fertility while protecting the plants from a number of biotic and abiotic stresses. Residing within plant, endophytes are unique group of symbionts that systematically invade the internal environment of host without causing any pathogenic symptoms. Endophytes, which include bacteria, fungi, and viruses, have been shown to have beneficial effects on their hosts, either directly or indirectly. On the other hand, Zingiberaceae is a valuable family of ginger that has a lot of economic benefits. Endophytes isolated from the Zingiberaceae plants are known to promote plant development through the production of phytohormone, 1- aminocyclopropane -1 carboxylic acid (ACC) deaminase, siderophore and also assist the host plant in phosphate solubilization activity. They are also prominent producers of several secondary metabolites with a lot of bioactivities. However, the full potential of endophytes from the Zingiberaceae plants largely remain untapped. Thus, the aim of this review is to discover various types of endophytes isolated from the Zingiberaceae plants, their phytohormone production, nutrient acquisition, biohardening application, secondary metabolites production and bioactivities. The broad knowledge of endophytes from Zingiberaceae plants will provide insight into new economic potentials and determine its future in sustainable agriculture practices.